Intellectual Capital and Capital Structure Effect on Firms Financial Performances - Suryani, Ani Wilujeng; Nadhiroh, Alfin (Journal of Accounting Research, Organization and Economics, 2020)
Objective This study aims to determine the influence of intellectual capital and capital structure on financial performance in manufacturing companies in Indonesia. Design/methodology The data were collected from all 140 manufacturing companies from 2015 to 2019. While most studies of intellectual capital were conducted by using multiple regression analysis, we investigate the impact of intellectual capital and capital structure on the financial performance by using weighted least square regression.Results The results showed that intellectual capital has a significant positive effect on firms financial performances, but the capital structure has a negative effect. The results of this study are beneficial for managers to consider increasing intellectual capital to create a competitive advantage in the midst of fierce competition of the ASEAN Economic Community era. In addition, managers need to consider the optimum capital structure to fulfill funding needs, hence financial distress can be minimized.Limitation/Suggestion - This study is a quantitative study limited to the availability of the data. Also, a number of outliers were found in the data and treated prior to the analysis.